IMPLEMENTASI PROGRAM POJOK PITU DALAM PEMENUHAN HAK ATAS KESEHATAN BAGI ORANG DENGAN GANGGUAN JIWA DI DESA SAMBIBULU, SIDOARJO - Safitri, Dhea Rachma; Setyowati, Raden Roro Nanik (Universitas Negeri Surabaya (Unesa), 2024)
Mental health plays an important role in efforts to achieve social equality, health coverage, access to human rights justice, and continued economic growth. The increase in the number of ODGJ has certainly become a special concern for the government to increase the realization of the rights of ODGJ, especially related to the right to health through the provision of health services that have been stipulated in Law No. 18 of 2014 which was later merged into Law No. 17 of 2023. The POJOK PITU program is one of the media as a form of fulfillment of the right to health through health services that have been provided. The purpose of this study is to (1) analyze the implementation of the POJOK PITU program, to find out (2) supporting factors and inhibiting factors, and (3) the impact of the implementation of the POJOK PITU program in fulfilling the right to health for people with mental disorders in Sambibulu village, Sidoarjo. This research uses a qualitative approach with descriptive methods. Data were collected using participatory observation techniques, structured interviews, and documentation. There are 2 sources of research, namely primary data sources, namely medical personnel, cadres, families and ODGJ, secondary data sources from books or records that are relevant to the research. The results showed that the implementation of the POJOK PITU program in fulfilling the right to health for ODGJ in Sambibulu village went well in terms of the four elements of the George Edward III model of policy implementation theory.